2006
DOI: 10.1016/j.immuni.2006.05.012
|View full text |Cite
|
Sign up to set email alerts
|

The Tec Family Tyrosine Kinases Itk and Rlk Regulate the Development of Conventional CD8+ T Cells

Abstract: The Tec family tyrosine kinases, Itk and Rlk, are expressed in thymocytes and peripheral T cells and regulate thresholds of T cell receptor signaling. Yet little is known about the specific role of Itk- and Rlk-dependent signals in CD8(+) T cell maturation. We show here that Itk(-/-) and Rlk(-/-)Itk(-/-) mice were nearly devoid of conventional CD8(+) T cells and, instead, contained a large population of CD8(+) T cells that bear striking similarity to lineages of innate lymphocytes. Itk(-/-) and Rlk(-/-)Itk(-/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
226
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(247 citation statements)
references
References 54 publications
21
226
0
Order By: Relevance
“…5B). Interestingly and as shown in Itkand Rlk/Itk-deficient CD8 + T cells [41,42], Eomesodermin mRNA expression was dramatically increased in Dok-1 transgenic CD8 + thymocytes (Fig. 5C).…”
supporting
confidence: 72%
See 1 more Smart Citation
“…5B). Interestingly and as shown in Itkand Rlk/Itk-deficient CD8 + T cells [41,42], Eomesodermin mRNA expression was dramatically increased in Dok-1 transgenic CD8 + thymocytes (Fig. 5C).…”
supporting
confidence: 72%
“…The phenotype of CD8 + CD44 high CD122 high T cells in Dok-1 transgenic mice is very similar to that of innate-like CD8 + thymocytes that accumulate in Itk-deficient mice [41,42]. We crossed Dok-1 transgenic mice with SAP-deficient mice to evaluate whether, as shown for Itk −/− mice [43], SAP was required for the development of these innate-like CD8 + T cells.…”
Section: Sap Is Required For the Development Of The Cd8 + Innate-likementioning
confidence: 99%
“…It has recently been shown that Tec kinases regulate the development of CD8 ϩ CTLs in this animal model (32,33). Studies of CD8 ϩ T cell function in Itk-deficient mice have reported a disparity between the in vitro responses of these cells and the in vivo responses of these mice to viral infections (30,31).…”
Section: Discussionmentioning
confidence: 96%
“…Recently, we found aberrantly high expression of eomesodermin in CD8 ϩ thymocytes and T cells from Itk Ϫ/Ϫ and Itk/Rlk Ϫ/Ϫ mice (37). Therefore, we also examined Itk Ϫ/Ϫ and Itk/Rlk Ϫ/Ϫ NKT cells for eomesodermin mRNA expression.…”
Section: Tec Family Kinase-deficient Nkt Cells Show Impaired Survivalmentioning
confidence: 98%
“…Although Itk and Rlk are dispensable for the development of CD8 ϩ innate T cells (37)(38)(39), the role of Tec family kinases has not been thoroughly studied in other subsets of innate T cells, such as NKT cells. One previous study demonstrated a role for Itk in NKT cell development, indicating impaired progression of Itk Ϫ/Ϫ NKT cells to stage 3 and a resulting decrease in NKT cell numbers (40).…”
mentioning
confidence: 99%